107k views
2 votes
Translate to an equation and solve the following: The difference of p and one-sixth is two-thirds.

User Draegtun
by
5.7k points

2 Answers

5 votes

Answer:

p = 5/6

Explanation:

For this problem, simply take the words of the problem and convert them into an equation as such:

The difference of p and one-sixth implies --> p - 1/6

is two-thirds implies --> 2/3

So, our equation:

p - 1/6 = 2/3

Now simply solve for p, and combine the fractions.

p - 1/6 = 2/3

p - 1/6 + 1/6 = 2/3 + 1/6

p = 2/3 + 1/6

p = 4/6 + 1/6

p = 5/6

Cheers.

User Vanhooser
by
5.0k points
6 votes

Answer: 5/6

Explanation:

p - 1/6 = 2/3

+1/6 +1/6

p = 5/6

User Dwardu
by
5.8k points